2021
DOI: 10.1177/1357633x20985391
|View full text |Cite
|
Sign up to set email alerts
|

Using telemedicine to facilitate social distancing in otolaryngology: A systematic review

Abstract: Objectives As the coronavirus 2019 pandemic puts strains on current models of otolaryngology practice, telemedicine is an attractive way for otolaryngologists to reduce in-person appointments while still addressing the health of their patients. This systematic review of the literature aims to identify the evidence basis for using telemedicine in otolaryngology practice to limit person-to-person interactions while achieving comparable quality to in-person services. Methods The authors gathered articles from thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…3 Part of the shift in practice included a sharp uplift in the use of telemedicine in place of face-to-face outpatient appointments. 4,5 Patients referred from primary care to secondary care with suspected head and neck cancer (HNC) are at particular risk of harm from changes to the standard-of-care diagnostic pathway. In normal times, physical examination, combined with flexible transnasal endoscopy of the upper aerodigestive tract where indicated, is considered an essential facet of the new patient evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Part of the shift in practice included a sharp uplift in the use of telemedicine in place of face-to-face outpatient appointments. 4,5 Patients referred from primary care to secondary care with suspected head and neck cancer (HNC) are at particular risk of harm from changes to the standard-of-care diagnostic pathway. In normal times, physical examination, combined with flexible transnasal endoscopy of the upper aerodigestive tract where indicated, is considered an essential facet of the new patient evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Part of the shift in practice included a sharp uplift in the use of telemedicine in place of face-to-face outpatient appointments. 4,5 Patients referred from primary care to secondary care with suspected head and neck cancer (HNC) are at particular risk of harm from changes to the standard-of-care diagnostic pathway. In normal times, physical examination, combined with flexible transnasal endoscopy of the upper aerodigestive tract where indicated, is considered an essential facet of the new patient evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the literature has expanded on the implementation and satisfaction in otolaryngology telemedicine [ 6 , 16 ] [ [6] , [16] , [17] , [18] ] [ [6] , [16] , [17] , [18] ]. A systematic review by Moentmann et al found that out of 35 articles that met inclusion, 32 (91.4%) of them had an effective telemedicine platform, compared to in-person appointments [ 19 ]. Darr et al performed a retrospective review of a satisfaction survey given from mid-March to mid-June 2020 called the modified pediatric otolaryngology telemedicine satisfaction survey (POTSS) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%